2006
DOI: 10.1063/1.2207571
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature high-pressure preparation of transparent nanocrystalline MgAl2O4 ceramics

Abstract: Transparent MgAl2O4 spinel nanoceramics have been sintered at relatively low-temperature (500–700°C) under high pressure (2–5GPa) using a hydrostatic press with high-temperature-calcined nanopowders. The morphology, nanostructure, optical property, and density of ceramics were analyzed by scanning electron microscopy, transmission electron microscopy, UV-VIS-IR transmission spectrum, and Archimedes draining method. The average grain size (<100nm for all samples sintered) depends on the sintering pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 23 publications
(14 reference statements)
2
55
0
Order By: Relevance
“…These authors have synthesized spinel powders which subsequently formed by cold isostatic pressing and sintered in a hot pressing machine by applying a mechanical pressure of 4 MPa obtaining a transparent material. Lu et al, (2006) have obtained a transparent spinel material after sintering at low temperature and high pressure (2-5 GPa). Morita et al, (2008) have obtained a transparent spinel material after sintering at 1300ºC in plasma sintering equipment (Spark Plasma Sintering, SPS), reaching 47% of transmittance at 550nm.…”
Section: Ceramic Materialsmentioning
confidence: 99%
“…These authors have synthesized spinel powders which subsequently formed by cold isostatic pressing and sintered in a hot pressing machine by applying a mechanical pressure of 4 MPa obtaining a transparent material. Lu et al, (2006) have obtained a transparent spinel material after sintering at low temperature and high pressure (2-5 GPa). Morita et al, (2008) have obtained a transparent spinel material after sintering at 1300ºC in plasma sintering equipment (Spark Plasma Sintering, SPS), reaching 47% of transmittance at 550nm.…”
Section: Ceramic Materialsmentioning
confidence: 99%
“…13 Simultaneously, much work has been done on the structural, electronic and optical properties of MgAl 2 O 4 and ZnAl 2 O 4 over the past few years. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] The effect of point vacancies on the spectral properties of MgAl 2 O 4 has been studied by S. L. Jiang et al 14 They revealed that the absorption peak at 5.3 eV is attributed to the neutral oxygen vacancy V o 0 , while two peaks at 3.2 eV and 4.75 eV are attributed to the 1+ charged oxygen vacancy V o 1 + . A related mechanism of transparency in MgAl 2 O 4 nanoceramics prepared by sintering under high pressure and low temperature has been studied by J. Zhang et al 15 , who suggested that the decrease in the transparency with increasing temperature (>700°C) is therefore a result of the light scattering at large pores.…”
Section: Introductionmentioning
confidence: 99%
“…A related mechanism of transparency in MgAl 2 O 4 nanoceramics prepared by sintering under high pressure and low temperature has been studied by J. Zhang et al 15 , who suggested that the decrease in the transparency with increasing temperature (>700°C) is therefore a result of the light scattering at large pores. The low-temperature, high-pressure preparation of transparent nanocrystalline MgAl 2 O 4 ceramics has been investigated by T. C. Lu et al, 16 indicating that the nanoceramics are highly transparent even though their relative densities are all less than 99 %, owing to the low or negligible light scattering from the nanosized grains and pores. The optical properties of ZnAl 2 O 4 nanomaterials obtained by the hydrothermal method have been investigated by Miron and co-workers, 17 demonstrating that the band gap is determined from the absorbance spectra, and it depends strongly on the temperature used for further heating the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Two-step sintering has a short high temperature sintering followed by a long low temperature treatment to frozen the grain boundary migration, which can obtain nanocrystalline ceramics [10]. Microwave and ultra-high pressure sintering are recognized as two effective routes to fabricate ceramics by sintering the nanopowder [11,12]. Despite these achievements, obstacles remain on the path forward to widespread deployment of dense nanocrystalline ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]. A number of nanocrystalline ceramics have been fabricated by using spark plasma sintering (SPS) [7,8], two-step sintering [9,10], microwave sintering [11], ultra-high pressure sintering [12], and so on [13,14]. SPS is used as a good method of preparing ceramics with pure phase because of short duration within sintering process [15].…”
Section: Introductionmentioning
confidence: 99%